Directions for improving economic efficiency in the use of engineering communications in housing construction in Uzbekistan - Nozima Nigmatjonova Ulamasjanovna (Genius Journals, 2023)
This article focuses on enhancing economic efficiency in the utilization of engineering communications in housing construction within the context of Uzbekistan. It examines the challenges associated with infrastructure development and proposes methods to optimize resource allocation, streamline processes, and ensure sustainable growth. The article presents a comprehensive analysis of the results obtained from implementing these methods and discusses their implications for the construction industry and overall economic development. Finally, the article concludes with recommendations to further enhance economic efficiency in engineering communications for housing construction
Keywords: Economic efficiency; engineering communications; housing construction